HUBUNGAN ANTARA GANGGUAN KOGNITIF DENGAN ACTIVITY OF DAILY LIVING (ADL) PADA LANSIA DI GRIYA LANSIA JANNATI KOTA GORONTALO - Nur Ayun R. Yusuf; Rosmin Ilham; Lisya Muksin (An Idea Health Journal, 2025)
Cognitive impairment is a serious problem because it can interfere with older people's daily activities and independence. Entering old age, individuals have the potential to experience changes in character. This is related to the decline in cognitive abilities which will result in difficulties in carrying out their activities, thereby allowing older people to become dependent on others. This research aimed to determine the relationship between cognitive impairment and Activity of Daily Living (ADL) in older adults at Griya Lansia Jannati Gorontalo City. This quantitative study uses descriptive correlational research methods with a cross-sectional design with a population of 30 and a sample of 30 older adults with a sampling technique, namely total sampling. The research instrument for measuring Cognitive Impairment uses a questionnaire (MMSE), while for measuring Activity of Daily Living using the Katz Index questionnaire. Bivariate analysis used the Spearmen's Rank test. The study results showed no cognitive disorders in the elderly, 12 (40.0%), and activities of daily living, namely independence, a total of 13 (43.3%). The conclusion is that there is a relationship between cognitive impairment and activity of daily living (ADL) in older people at Griya Lansia Jannati Gorontalo City with (P-value = 0.001) <?=0.05. This research is expected to serve as a reference and literature in gerontic nursing so that nurses, caregivers, and the managers of Griya Lansia Jannati can provide interventions that improve cognitive abilities and activities of daily living (ADL) in older people.